2023
DOI: 10.3390/cancers15061641
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Selectively Inhibits Detachment of Metastatic Thyroid Cancer Cells during Random Positioning

Abstract: We recently reported that synthetic glucocorticoid dexamethasone (DEX) is able to suppress metastasis-like spheroid formation in a culture of follicular thyroid cancer (FTC)-133 cells cultured under random positioning. We now show that this inhibition was selective for two metastatic thyroid carcinoma cells, FTC-133 and WRO, whereas benign Nthy-ori 3-1 thyrocytes and recurrent ML-1 follicular thyroid cancer cells were not affected by DEX. We then compare Nthy-ori 3-1 and FTC-133 cells concerning their adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 91 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…A new study by Melnik et al [ 185 ] demonstrated that this inhibition was selective for two metastatic thyroid cancer-cell lines, FTC-133 and WRO, whereas benign Nthy-ori 3-1 thyrocytes and recurrent ML-1 follicular thyroid cancer cells were not affected by DEX (0, 10, 100, 1000 nM) when exposed for 72 h to the RPM ( Table 9 ). DEX disrupts random positioning-triggered p38 stress signaling in FTC-133 cells [ 185 ]. DEX treatment of FTC-133 cells is associated with enhanced adhesiveness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new study by Melnik et al [ 185 ] demonstrated that this inhibition was selective for two metastatic thyroid cancer-cell lines, FTC-133 and WRO, whereas benign Nthy-ori 3-1 thyrocytes and recurrent ML-1 follicular thyroid cancer cells were not affected by DEX (0, 10, 100, 1000 nM) when exposed for 72 h to the RPM ( Table 9 ). DEX disrupts random positioning-triggered p38 stress signaling in FTC-133 cells [ 185 ]. DEX treatment of FTC-133 cells is associated with enhanced adhesiveness.…”
Section: Resultsmentioning
confidence: 99%
“…This process is caused by the restored, pronounced formation of a normal number of tight junctions. In addition, RPM-exposed Nthy-ori 3-1 and ML-1 cells exhibit an elevation in the anti-adhesion protein mucin-1, which might be a protection mechanism against mechanical stress [ 185 ]. The balance between adhesion, anti-adhesion, and cell–cell connections enables the detachment of adherent human cells exposed to the RPM or not, allowing selective inhibition of thyroid in vitro metastasis by DEX [ 185 ].…”
Section: Resultsmentioning
confidence: 99%
“…Melnik et al [ 23 ] used a random-positioning-based metastasis model [ 24 ] to study the inhibitory effects of dexamethasone in more detail. The team of authors demonstrated that mechanical stress plays an important role in this in vitro model with follicular thyroid carcinoma (FTC) cells and that tumor cells not derived from metastases respond differently to this stress when compared to healthy or recurrent cells.…”
Section: Updates On Models Mimicking Physiological Processesmentioning
confidence: 99%
“…The procedure was performed in the same way as described in [18]. To obtain sufficient mRNA out of the cells grown in channel slides, a higher cell number of 40,000 cells/cm 2 and a µ-Slide, 0.8 Luer, ibiTreat (ibidi) were used.…”
Section: Mrna Isolation and Quantitative Real-time Pcr (Ftc-133)mentioning
confidence: 99%
“…The samples were measured in triplicate and evaluated by using the comparative threshold cycle (∆∆C T ) method. 18S rRNA was used as the housekeeper reference due to its stable expression in dynamic FTC-133 cell cultures [18].…”
Section: Mrna Isolation and Quantitative Real-time Pcr (Ftc-133)mentioning
confidence: 99%